Occupational analysis and group process - O'Brien, Jane Clifford (Elsevier/Mosby, 2013)
Get the best instruction on occupational analysis, group process, and therapeutic media - all from one book! Using a matter-of-fact style to share their experiences, successes, and failures, expert authors Jane Clifford O'Brien and Jean W. Solomon provide you with effective therapeutic media; sample activity analyses useful in current health care contexts; practical guidance in play, leisure, and social participation areas of occupation; strategies for effective group management and processes; and overviews of theories supporting best practice.